ANALISIS SEMIOTIK PERUBAHAN PERSEPSI MASKULINITAS DALAM IKLAN MINUMAN SUPLEMEN INDONESIA - Sussieyani, Anis (Universitas Pendidikan Indonesia, 2018)
The development of reformation era has provided diverse discourses of masculinity that develop in Indonesia society. This paper aims to examine the changing perceptions of masculinity in Indonesia supplementary beverage advertising. Based on the theory of semiotics expressed by Roland Barthes, this paper examines the changing perceptions of masculinity reflected on five ads of Extra Joss for â€œQurbaniâ€ (the day of sacrifice) edition. This paper will analyze the symbols of masculinity through the use of linguistic and visual elements in the advertisement.The result showed that there had been changes in the perceptions of masculinity in Extra Joss ads for â€œQurbaniâ€ or the day of sacrifice edition. Four advertisements made before 2017 showed the image of masculinity characterized by the glorification of body strength, aggressiveness, and fearless attitude of men. This value of masculinity is also marked through the use of aggressive linguistic markers such as the use of the word laki, fearless, penjinak, etc. However, one advertisement that was created in 2017 showed a softer image of masculinity. It was marked by warmth and togetherness behaviors of men generated by the male model in the ad. This was reinforced by the emergence of female characters in the ad. The analysis also showed that these masculinity changes were influenced by K-Pop globalization which generated a softer masculinity than previous advertisements. In addition, the analysis also showed changes in the meaning of â€œQurbaniâ€ (sacrifice) in the ads. Previously, it was marked as something that was achieved and struggled. However, nowadays â€œQurbaniâ€ or sacrifice is seen as a joyful activity.